(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The epigraphic testimonies regarding the worship of Reue in the western half of the conuentus Bracarum, where alternative theonymic forms (Reo, Reoue and Rego) assume prominence, are presented and discussed.